Prioritization of Alternative Agricultural Products Based on Market Signals as a Tool for the Development of Innovative Projects - D. Villalva-Bustamante; M. F. Logroño-Rodríguez; T. F. Flores-Pulgar; B. Naula-Erazo (ESPOCH Congresses)
The Decentralized Autonomous Government of the province of Chimborazo promotes the agricultural productive development of the province by promoting entrepreneurship, and improving the capacities of producers, access to production factors, and integration of actors and subjects of agriculture and management on the basis to strategic planning. The construction of the Chimborazo Competitiveness Agenda was a participatory process that identified opportunities to improve the agricultural sector, where agricultural production at the primary level was recognized as a vocation and strength of the province; however, a strategic necessity was to establish possibilities of adding value and diversifying agricultural production. The definition of a set of agricultural products with high potential at the primary level and/or in agroindustrial processes that are not deeply explored required determining market signals to identify new medium- and long-term commercial possibilities for Chimborazo farmers. Additionally, it was recognized that the management of the province of Chimborazo was based on its management of the Millennium Development Goals, the Constitution of the Republic, the National Plan for Development in a Supra-Provincial Framework, as well as the Plan Development of Chimborazo, the Territorial Planning Plan and others that promoted planning with a focus on territorial and solidarity sustainable development.